Distribution of Trichostrongylus colubriformis on common pasture grasses and legumes from the Midwestern United States - Katy A. Martin; Jeba R.J. Jesudoss Chelladurai; Christina Lavery; Rachel Shelangoski; Matthew Chaffee; Matthew T. Brewer (PLoS ONE, 2025)
Nematodes that infect grazing herbivores rely on the ability of larvae to escape the fecal pat and ascend onto forage in order to be eaten by a subsequent host. However, pastures are polycultures of grasses and forbs that vary with respect to morphology and potential innate defense mechanisms acquired as part of their own co-evolution with nematode parasites. The objectives of this study were to 1) characterize the vertical distribution of Trichostrongylus colubriformis on a variety of plant species found in pastures in the Midwestern United States and 2) to identify plants that enhanced or inhibited larval ascent. Climbing assays were performed under greenhouse conditions whereby L3 were directly recovered from foliage. We found that at least 50% or more of the larvae were distributed on the first 2.5 cm closest to the soil surface for all plant species tested. In contrast, less than 10% of the larvae were distributed 12 cm or higher. For practical purposes, our findings agree with previous studies that suggest limiting grazing below a certain height to decrease parasite consumption. Further nuanced studies are needed to identify individual plant mechanical and chemical defenses that impact the ecology nematodes of veterinary importance.